Caribbean development to the year 2000 : challenges, prospects and policies - Bourne, Compton (Commonwealth Secretariat LondonGB, 1988)
Assesses economic development performance and economic policies of the Region. Reviews world economic trends from the perspective of the Caribbean Community. Analyses demographic and human resource prospects of the Community. Discusses aggregate financial performance, requirements and prospects focusing on investment, savings and foreign capital. Analyses foreign trade performance and prospects. Discusses inter alia, demand and supply, imports and exports, protection and South-South trade. Contains analyses of production in 4 sectors viz. agriculture, agro-industry, manufacturing and tourism. Discusses policy opportunities, requisites and strategies, draws policy conclusions and makes recommendations.